Impacts of L-Arginine on Haematological and Serum Biochemical Indices of Rats Exposed to Chlorpyrifos - Akande, Motunrayo Ganiyat; Oladele, Gbenga Michael; Mikail, Hudu Garba; Adeniran, Lateef Ariyo; Chibuogwu, Ijeoma Chika (British Journal of Healthcare and Medical Research, 2025)
Chlorpyrifos is an organophosphorus insecticide that is applied expansively for pest control and its usage has been linked to several cases of poisoning. L-arginine is an α-amino acid that is crucial in protein biosynthesis and it has been reported to exert bioprotective effects in the body. The research was conducted in order to find out the impacts of L-arginine (AG) on haematological and serum biochemical indices in male Wistar rats exposed to chlorpyrifos. Thirty five rats were distributed into five groups. They received the following treatments by oral gavage for 28 days: distilled water [DT group], olive oil [LV; 1 ml/kg], chlorpyrifos (CF group; 8.5 mg/kg), L-arginine (AG; 100 mg/kg), chlorpyrifos (8.5 mg/kg)+L-arginine (100 mg/kg). The rats were sacrificed after the termination of the research. Subsequently, haematological and serum biochemical parameters were assessed. A significant (p < 0.05) reduction in the MCV of the CF group compared to the LV group was observed. Additionally, a substantial (p < 0.05) elevation was recorded in the MCHC of the CF group relative to the AG group. There were significant reductions in the calcium levels, while the magnesium levels were remarkably elevated in the CF and CF+AG groups compared to the DT and LV groups respectively. However, no significant alteration was noticed in the serum oxidative stress parameters (malondialdehyde, catalase and superoxide dismutase) that were analyzed. In this study, CF disrupted some haemato-biochemical parameters while AG minimally suppressed its effects. Further studies are warranted to expound the mechanisms of toxicity of CF, and the bioprotective propensity of AG.